Menilai Efisiensi Operasional Perusahaan melalui Net Profit Margin dalam Tinjauan Kritis Berbasis Literatur - Riska Ainur Rosyida; Zulfaa Gunawan; Zahra Gunawan; Cynthia Eka Violita (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2026)
Net Profit Margin (NPM) is a profitability ratio that is widely used to assess a company's operational efficiency because it reflects the company's ability to control costs and convert sales into net profit. This study uses a qualitative descriptive literature review method by synthesizing national and international scientific articles that discuss NPM, profitability ratios, and company operational efficiency. The results of the study show that NPM is consistently used as the main indicator in assessing operational efficiency, but high sales are not always followed by an increase in NPM. In addition, repeated fluctuations in NPM indicate instability in operational efficiency even though the company is profitable. The novelty of this study lies in the identification of a conceptual pattern that positions NPM not only as a measure of static profitability, but also as a diagnostic tool for assessing the sustainability of a company's operational efficiency in the medium and long term. These findings contribute academically by enriching the understanding of the strategic role of NPM in evaluating a company's operational and financial performance.